2011
DOI: 10.1016/j.pec.2010.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Sharing vs. caring—The relative impact of sharing decisions versus managing emotions on patient outcomes

Abstract: Objective: To assess the relative impact of cognitive and emotional aspects of shared decision making (SDM) on patient outcomes. Practice Implications: It is important that doctors focus on both sharing decisions and managing emotions in consultations. Communication skills training addressing both these areas may be an effective way to improve diverse patient outcomes. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 34 publications
1
43
0
2
Order By: Relevance
“…Although Smith et al [28] found substantial correlations with patient satisfaction, no association was found by Goossenen et al [13] and Butow et al [23]. However, the latter study reported moderate correlations between OPTION and the Satisfaction with Decision Scale four months after the initial consultation.…”
Section: Correlation With Other Measuresmentioning
confidence: 87%
See 1 more Smart Citation
“…Although Smith et al [28] found substantial correlations with patient satisfaction, no association was found by Goossenen et al [13] and Butow et al [23]. However, the latter study reported moderate correlations between OPTION and the Satisfaction with Decision Scale four months after the initial consultation.…”
Section: Correlation With Other Measuresmentioning
confidence: 87%
“…Additionally, convergence of observation-based ratings of patient involvement in decision making (original OPTION score) and observation-based ratings of actual patient involvement (e.g., number of questions) should be expected (see Kasper et al in this issue). Another validation approach would include the examination of OPTION scores with regard to meaningful patient outcomes [28]. Moreover, the performance of SDM competencies assessed by OPTION should be tested concurrently by comparing OPTION scores with more general aspects of physician-patient communication from other observation-based measures (e.g., Roter Interaction Analysis System [47], Four Habits Coding Scheme [48], and Medical Interaction System [49]).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…As highlighted by Smith et al, it is important that doctors focus on both instrumental tasks, such as sharing decisions, and emotion management in consultations [26]. This is the first time evidence has been provided to support that timing, that is, 'when to do what' rather than 'what should be done', has become crucial to clinical practice, which has the potential to influence patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…PCC may also influence the patients' level of emotional distress; however, the evidence is rather small and inconclusive. Whereas physicians' empathy have been associated with less patient distress in some studies [10] [11] [12], other studies have found that empathy was associated with increased patient distress after their visit [13]. Moreover, other studies found no associations [14] [15].…”
Section: Introductionmentioning
confidence: 99%